2022
DOI: 10.1108/mip-03-2022-0117
|View full text |Cite
|
Sign up to set email alerts
|

Green pride in sustainable versus premium brand decisions

Abstract: PurposeEarlier research indicates that brand choices may display different identity signals, such as altruism and benevolence for green brands or high status and exclusiveness for premium brands. This research adds to the literature by exploring how opting for green (vs premium) brands leads consumers to feel authentic (vs hubristic) pride.Design/methodology/approachThree experimental studies were conducted to test the hypotheses related to green versus premium choices (Studies 1–3), public accountability (Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
1
0
1
Order By: Relevance
“…In their study, Wei et al [64] concluded that consumers' recycling efforts positively influence their feelings of pride. These studies align with a recent trend of research exploring the relationship between sustainable consumption and the feeling of pride in depth [65][66][67]. Hence, the following hypothesis was assumed: H4.…”
Section: Feelings Of Pridesupporting
confidence: 75%
“…In their study, Wei et al [64] concluded that consumers' recycling efforts positively influence their feelings of pride. These studies align with a recent trend of research exploring the relationship between sustainable consumption and the feeling of pride in depth [65][66][67]. Hence, the following hypothesis was assumed: H4.…”
Section: Feelings Of Pridesupporting
confidence: 75%
“…Our results indicate that mechanisms for promoting the eco-branding of the studied region's industrial complex should help to take a fresh look at the problems of company management in related industries [59][60][61][62][63][64][65][66]. In this, we share the views of scholars who explore the possibilities of accelerating the transformation of socio-economic systems according to ESG principles [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 61%
“…Thus, positive perceptions about a corporation shaped by its CSR activities boost employees' pride (John et al 2017) and intention to support its brand reputation (Ellemers et al 2004;Hur et al 2018). Employees are increasingly likely to experience pride when they realize that customers opt for their green brand, making them feel proud to contribute to pro-environmental and pro-social endeavors (Maior et al 2022). Moreover, our study argues that GHRM is correlated (i.e., as an antecedent) to organizational pride (Kuo et al 2016;Kim et al 2020).…”
Section: Green Human Resources Management (Ghrm) and Organizational P...mentioning
confidence: 79%